Opportunities for and constraints to safe and sustainable vegetable production in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Kumara, G. D. K.; Wijetunga, C. S.; Madhuwanthi, Piumi; Duleesha, Nisansala (International Water Management Institute (IWMI). CGIAR Initiative on Fruit and Vegetables for Sustainable Healthy Diets, 2023)
Sri Lanka is blessed with ideal conditions for cultivating a wide variety of fruits and vegetables. The country has around 80 varieties produced in different agroecological zones. There are several government and private organizations supporting vegetable farmers and farmers are organized into formally registered organizations. However, the average consumption of fruits and vegetables in Sri Lanka is around 150 g per day and per capita consumption is approximately 112 g per day, which is 50% lower than the World Health Organization (WHO) recommendations (SAARC 2017). For a healthy and prosperous nation, the production and consumption of fruits and vegetables are important. Our research set out to identify opportunities and barriers for sustainable and year-round vegetable production. The findings are based on two multistakeholder consultations, a gendered field survey conducted in 18 villages through separate women and men focus group discussions (FGDs), key informant interviews in Welimada and Balangoda Divisional Secretariat Divisions, and a comprehensive literature review. The study focused on upcountry temperate zone vegetables.